Advisory Committee endorses CTA's evolution - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Throughout the first week of June, CTA's Advisory Committee held its annual meeting at the organisation's headquarters in Wageningen, the Netherlands. With Members from thirty ACP and EU countries, the Advisory Committee represents all six regions...